Microbial Community Structures and Important Associations Between Soil Nutrients and the Responses of Specific Taxa to Rice-Frog Cultivation - Yi, Xiaomei; Yi, Kai; Fang, Kaikai; Gao, Hui; Dai, Wei; Cao, Linkui (Frontiers in Microbiology, 2019)
Rice-frog cultivation is a traditional farming system in China and has been reintroduced as an agricultural practice in China in recent years. The microbial community in paddy rhizospheric soils has attracted much attention because many microorganisms participate in functional processes in soils. In this study, Illumina MiSeq sequencing-based techniques were used to investigate soil microbial communities and functional gene patterns across samples obtained by conventional rice cultivation (CR) and rice-frog cultivation (RF). The results showed that RF significantly affected the microbial community composition and richness, which indicated that the rhizospheric microorganisms responded to the introduction of tiger frogs into the paddy fields. Operational taxonomic units (OTUs) from Sandaracinaceae, Anaerolineaceae, Candidatus Nitrososphaera, Candidatus Nitrosotalea, Candidatus and Nitrosoarchaeum and some unclassified OTUs from Euryarchaeota and Agaricomycetes were significantly enriched by RF. The abiotic parameters soil organic carbon (SOC), nitrate nitrogen (NO3–N) and available phosphorus (AP) changed under RF treatment and played essential roles in establishing the soil bacterial, archaeal and fungal compositions. Correlations between environmental factors and microbial communities were described using network analysis. SOC was strongly correlated with Anaerolineaceae, Methanosaeta and Scutellinia. NO3–N showed strong positive correlations with Opitutus, Geobacter, and Methanosaeta. NH4+-N was strongly positively associated with Sideroxydans, and TN was strongly positively correlated with Candidatus Nitrotoga. Compared to conventional CR, RF greatly enriched specific microbial taxa. These taxa may be involved in the decomposition of complex organic matter and the transformation of soil nutrients, thus promoting plant growth by improving nutrient cycling. The unique patterns of microbial taxonomic and functional composition in soil profiles suggested functional redundancy in these paddy soils. RF could significantly affect the bacterial, archaeal and fungal communities though changing SOC and AP levels.